2020
DOI: 10.1177/1747954120971755
|View full text |Cite
|
Sign up to set email alerts
|

Servant leadership, leader effectiveness, and the role of political skill: A study of interscholastic sport administrators and coaches

Abstract: Servant leadership is a model of leadership based on ethics and benevolent service to others and has been associated with numerous positive outcomes for employees and organizations. Due to a limited number of studies examining servant leadership (SL) within sport, the purpose of this study was to investigate the relation of servant leadership and leader effectiveness outcomes in sport administration and to examine if political skill (i.e., how people influence others), was a moderator of servant leader effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Regarding the managers' perceptions of different relevant K/C/S in relation to the three main managerial levels, the participative nature of the sorting generated both transversal and specific characteristics of SM K/C/S, substantiated by the high collective consensus agreement for the emerged managerial competency models and the excellent internal consistency. Whilst high motivation, integrity, professionalism, formal academic achievements, respect for hierarchies and roles, and soft and technical skills were required for Entry level managers [18,19,60], Senior managers were expected to show strategic management, managing change, decision-making, risk management, planning and control skills, problem and conflict solving, networking, and leadership skills [55,[61][62][63][64][65][66]. Conversely, soft skills are central for all managerial levels to ensure working effectiveness because non-technical skills are highly valued in extremely competitive working environments, where most employees or candidates might possess comparable knowledge and qualifications [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the managers' perceptions of different relevant K/C/S in relation to the three main managerial levels, the participative nature of the sorting generated both transversal and specific characteristics of SM K/C/S, substantiated by the high collective consensus agreement for the emerged managerial competency models and the excellent internal consistency. Whilst high motivation, integrity, professionalism, formal academic achievements, respect for hierarchies and roles, and soft and technical skills were required for Entry level managers [18,19,60], Senior managers were expected to show strategic management, managing change, decision-making, risk management, planning and control skills, problem and conflict solving, networking, and leadership skills [55,[61][62][63][64][65][66]. Conversely, soft skills are central for all managerial levels to ensure working effectiveness because non-technical skills are highly valued in extremely competitive working environments, where most employees or candidates might possess comparable knowledge and qualifications [60].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these aspects represent the foundation of the SM professional practice and training [1,2,41,[74][75][76][77], traditionally embedded within formal and non-formal education. Additionally, leadership and political soft skills were perceived as relevant aspects that should be embedded in their vocational training [37,61,63,65,[78][79][80][81]. In considering that the participants in this study voluntarily engaged in a non-formal SM educational course tailored to ameliorate their future professional prospects, considerable attention should be given to the knowledge gaps that they emphasized in relation to the different managerial levels to constrict sound educational programs based on attendees' specific career stage, educational background and training needs.…”
Section: Discussionmentioning
confidence: 99%
“…Servant leadership is based on several values, including building corporate vision (Russell and Stone, 2002). Previous studies have also empirically identified a positive association between servant leadership and perceived leadership effectiveness (Robinson et al ., 2021). Therefore, we can reasonably speculate that followers of servant leaders would report higher levels of organizational vision and leadership effectiveness.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Since no robust measurement scales are currently in place in the sport domain, servant leadership research in the sport domain is considered to be in Phase 2, as Eva et al ( 2019 ) have pointed out. In addition to servant leadership research targeting athletes, research on coaches (Dahlin and Schroeder, 2021 ; Robinson et al, 2021 ; Vinson and Parker, 2021 ) and employees of sport organizations (Megheirkouni, 2020 ; Svensson et al, 2021 ; Swanson et al, 2022 ) has also accumulated.…”
Section: Literature Reviewmentioning
confidence: 99%